Tinnitus reaction index: A Measure to assess quality of life in individuals with tinnitus - Christy Martin; Sharda Ajay Sarda (Journal of All India Institute of Speech and Hearing)
The aim of the present study was to develop self-report questionnaire in Marathi which assess quality of life in individuals with tinnitus. Method involved selection of various questions for the development of Reaction Index" after reviewing various earlier questionnaire and the problems frequently faced by the individuals with tinnitus observed during case history. Initially 34 questions were included related to functional, emotional, and catastrophic reactions of the patient with tinnitus. It also had a new domain named indicator" which suggests about uctuations in the tinnitus/ variations in the level of tinnitus due to certain factors. After a pilot study on 15 individuals with tinnitus, the number of questions were ltered down to 20 in order to minimize the ambiguity and redundancy of the questionnaire. Second part of the study involved administering the questionnaire in 100 native Marathi speakers’ with complaint tinnitus. Test- retest reliability and split half reliability was found to be 0.834 and 0.742 respectively. Similarly validity was also found to be high (r = 0.84). Thus the developed tool TRI-Marathi is a reliable and valid subjective measure to assess the impact of tinnitus in Marathi speaking individuals and categorize the severity of their tinnitus into di erent degrees.